Simulating far infrared spectra of Zn1-xMnxSe/GaAs epifilms, MnSe/ZnSe superlattices and predicting impurity modes of N, P defects in Zn1-xMnxSe. Issue 1 (1st January 2016) - Talwar, Devki N.; Yang, Tzuen-Rong; Chou, Wu-Ching
Abstract: A comprehensive lattice dynamical study is reported to emphasize the vibrational behavior of perfect/imperfect zinc-blende (zb) ZnSe, MnSe and Zn1−x Mnx Se alloys. Low temperature far-infrared (FIR) reflectivity measurements performed on a series of molecular beam epitaxy grown Zn1−x Mnx Se/GaAs (001) epilayers have a typical 'intermediate-phonon-mode' behavior. Besides perceiving ZnSe- and MnSe-like TO-phonon resonances, the study also revealed a weak Mn alloy-disorder mode below MnSe band. A classical effective-medium theory of multilayer optics is used to evaluate dielectric tensors of both epilayers and substrate for simulating reflectivity and transmission spectra of ultrathin epifilms and superlattices at near normal and/or oblique incidence. In the framework of a realistic rigid-ion model and exploiting an average t -matrix Greens function (ATM-GF) theory we appraised the vibrational properties of nitrogen and phosphorous doped Zn-Mn chalcogenides. Lattice relaxations around isolated NSe (PSe ) defects in ZnSe and zb MnSe are evaluated by first principles bond-orbital model that helped construct perturbation models for simulating the localized vibrational modes (LVMs). Calculated shift of impurity modes for isotopic 14 NSe ( 15 NSe ) defects in ZnSe offered a strong revelation of an inflexible defect–host interaction. By retaining force constant change parameter of 14 NSe ( 15 NSe ) in heavily N-doped ZnSe, the ATM-GF theory predicted (a) three non-degenerate LVMs for the photoluminescence defect center V Se -Zn- 14 NSe ( V Se -Zn- 15 NSe ) of C s symmetry, and (b) six impurity modes for the second nearest-neighbor NSe -Zn-NSe pair defect of C 2v symmetry. From the range of simulated defect modes, we have ruled out the possibility of N-pairs and justified the presence of VSe -Zn-NSe complex centers – likely to be responsible for the observed large absorption bandwidth in highly N-doped ZnSe. High resolution measurements of FIR absorption and/or Raman scattering spectroscopy are needed to validate the accuracy of our theoretical conjectures. Abstract :